Understanding the pelvis : a functional approach to yoga - Franklin, Eric N. (Human Kinetics, 2020)
"The first part of the book covers anatomy and biomechanics of the pelvis, and the second part includes 26 exercises for yoga practitioners and students specifically focused on strengthening the pelvis"--